1993
DOI: 10.1002/malq.19930390151
|View full text |Cite
|
Sign up to set email alerts
|

Highness and bounding minimal pairs

Abstract: We show the existence of a high r.e. degree bounding only joins of minimal pairs and of a high 2 nonbounding r.e. degree. IntroductionAn important topic in the study of recursively enumerable sets and degrees has been the interaction between the jump operator and the order theoretic properties of an r. e. set A (in the lattice E of all r. e. sets) and of its degree a in R, the upper semilattice of the r. e. degrees. An early theme in this area was the idea that sets with "low" jumps should behave like the recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…(1) t is odd and all the af (6 E d(P)), including a: , are become undefined (since rf (2) t is even and either Case 5.1 holds for some Q < L P or some node < L P receives Note that in either case, a; is destroyed and enumerated into B. By Lemma 2.4(v), a: = a: 5 a :…”
Section: ~( P a )mentioning
confidence: 99%
See 1 more Smart Citation
“…(1) t is odd and all the af (6 E d(P)), including a: , are become undefined (since rf (2) t is even and either Case 5.1 holds for some Q < L P or some node < L P receives Note that in either case, a; is destroyed and enumerated into B. By Lemma 2.4(v), a: = a: 5 a :…”
Section: ~( P a )mentioning
confidence: 99%
“…degree c 5 a, there is a minimal pair of r.e. degrees ao, 01 below c. COOPER (see DOWNEY et al [2]) showed that one can choose a high, and DOWNEY, LEMPP and SHORE [2] showed that one can choose a high and a o V a 1 = c. LACHLAN [9] also showed that there exists a non-recursive r. e. degree such that below it there is no minimal pair of r.e. degrees.…”
mentioning
confidence: 99%
“…Cooper [2] showed that every high c. e. degree bounds a minimal pair. Downey, Lempp and Shore [3] showed that there exists a high 2 nonbounding degree. In relation to the noncupping property, Harrington [5] extended the Cooper-Yates Noncupping Theorem by showing that for each high c. e. degree h, there exists a high c. e. degree a < h such that for any c. e. degree x, if h ≤ a ∨ x, then h ≤ x; and Harrington [6] showed that there is a c. e. degree a = 0 such that for all c. e. degrees x, y, if 0 < x ≤ a ≤ y, then there is a c. e. degree z < y such that x ∨ z = y.…”
Section: Introductionmentioning
confidence: 99%
“…developed by Lerman [50], Downey, Lempp and Shore [22], with some technique to cope with the interactions between two kinds of strategies. This theorem implies several well-known results, such as Downey, Lempp and Shore's result [22] that there is a high 2 nonbounding c.e. degree.…”
Section: The Proof Of This Theorem Combines Seetapun's Construction Amentioning
confidence: 99%
“…degrees. Downey, Lempp and Shore [22] proved that nonhemimaximal sets can be high 2 . Furthermore, Downey and Stob [24] showed that jump inversion holds for hemimaximal sets.…”
Section: Downey and Stobmentioning
confidence: 99%